A bird's eye view of NK cell receptor interactions with their MHC class I ligands. Issue 1 (September 2015) - Saunders, Philippa M.; Vivian, Julian P.; O'Connor, Geraldine M.; Sullivan, Lucy C.; Pymm, Phillip; Rossjohn, Jamie; Brooks, Andrew G.
Summary: The surveillance of target cells by natural killer (NK) cells utilizes an ensemble of inhibitory and activating receptors, many of which interact with major histocompatibility complex (MHC) class I molecules. NK cell recognition of MHC class I proteins is important developmentally for the acquisition of full NK cell effector capacity and during target cell recognition, where the engagement of inhibitory receptors and MHC class I molecules attenuates NK cell activation. Human NK cells have evolved two broad strategies for recognition of human leukocyte antigen (HLA) class I molecules: (i) direct recognition of polymorphic classical HLA class I proteins by diverse receptor families such as the killer cell immunoglobulin‐like receptors (KIRs), and (ii) indirect recognition of conserved sets of HLA class I‐derived peptides displayed on the non‐classical HLA‐E for recognition by CD94‐NKG2 receptors. In this review, we assess the structural basis for the interaction between these NK receptors and their HLA class I ligands and, using the suite of published KIR and CD94‐NKG2 ternary complexes, highlight the features that allow NK cells to orchestrate the recognition of a range of different HLA class I proteins.